Using visuals in written texts - Mahliyo Saydaliyeva Ulug’bek qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
When comparing the directions of modern linguistics with the linguistics of the past centuries, it can be noticed that their number has increased significantly. The main reason for the expansion of the fields of linguistics is the integrated study of the phenomenon of language with other disciplines. We can cite sociolinguistics, pragmalinguistics, cognitive linguistics, communicative linguistics, etc. as examples of new directions of modern linguistics. Now, if we are going to talk about the relationship between the research topic and the directions of linguistics, it is appropriate to talk about psycholinguistics. Psycholinguistics is a science that studies the emergence of speech and its mental perception, the further formation of speech, and it originated from the union of psychology and linguistics. The founder of the science is the German linguist G. Shteinthal, whose most important work in the field is "Classification of language s and the classification of their laws of development". The psycholinguistic school emerged in the first half of the 19th century and the beginning of the 20th century and studied the functional features of language, language construction, and speech perception. Later, in psycholinguistics, the concept of linguistic consciousness became more and more refined and became one of the important objects of science. Linguistic consciousness is the planning and development of communication in the internal process and is inextricably linked with the concept of text, because the text is one of the highest units of communication. The process of psycholinguistic analysis of the text includes its functional and stylistic features. From this point of view, the following work is among the analytical methods of psycholinguistics.